2020
DOI: 10.1177/1457496920930142
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the low anterior resection syndrome score in finnish patients: preliminary results on quality of life in different lars severity groups

Abstract: Background and Aims: Low anterior resection syndrome is common after anterior resection for rectal cancer. Its severity can be tested with the low anterior resection syndrome score. We have translated the low anterior resection syndrome score to Finnish, and the aim of this study is to validate the translation. Materials and Methods: The translated Finnish low anterior resection syndrome score and European Organisation for Research and Treatment of Cancer quality-of-life questionnaire-C30 and QLQ-CR29 question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…found that patients with major LARS had a significantly lower quality of life and more defecatory symptoms than those with no low anterior resection syndrome. Significant differences in the global quality of life between those with no or minor LARS could not be detected, even in cases where a progression of defecatory symptoms was noted 13 . Thus, the patients in this study were categorized into a group with major LARS and a group with minor or no LARS.…”
Section: Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…found that patients with major LARS had a significantly lower quality of life and more defecatory symptoms than those with no low anterior resection syndrome. Significant differences in the global quality of life between those with no or minor LARS could not be detected, even in cases where a progression of defecatory symptoms was noted 13 . Thus, the patients in this study were categorized into a group with major LARS and a group with minor or no LARS.…”
Section: Methodsmentioning
confidence: 90%
“…Significant differences in the global quality of life between those with no or minor LARS could not be detected, even in cases where a progression of defecatory symptoms was noted. 13 Thus, the patients in this study were categorized into a group with major LARS and a group with minor or no LARS.…”
Section: Diagnosis and Classification Of Larsmentioning
confidence: 99%
“…This definition is too broad to clearly identify the diagnostic criteria because the symptoms of LARS are highly variable. Therefore, in clinical practice and in academic studies, the LARS score is used instead of the previous definition to diagnose LARS and estimate the severity of the disease [38].…”
Section: Diagnostic Criteria For Larsmentioning
confidence: 99%
“…Clinically validated standard 25 EORTC QLQ-C30 18 3 6 min walk test 19 3 Breast-Q Score 20 2 Quality of Recovery Score 21 2 COPD assessment test 22 1 Duchenne muscular dystrophy tests 23 1 Low Anterior Resection Syndrome Score 24 1 Wexner Incontinence Score 25 1 MRC Breathlessness Scale 26 1 Numerical Pain Rating Scale 27 1 Medical Outcomes Study SF-36 28 1 Oswestry Disability Index 29 1 Female Sexual Function Index 30 1 State-Trait Anxiety Inventory 31 1 MD Anderson Dysphagia Inventory 32 1 Expanded Prostate Cancer Index Composite 33 1 Functional Assessment of Cancer Therapy 34 1 Colorectal Functional Outcome Questionnaire 35 1 Hospital Anxiety and Depression Scale 36 1 Subjectively 1…”
Section: Methods Nmentioning
confidence: 99%